Lives in the law - Douglas, Lawrence; Sarat, Austin; Umphrey, Martha Merrill (University of Michigan Press, 2002)
Examines how the lives of individuals, social groups, and nations are fashioned by their engagement with the law.
Keywords: Sociological jurisprudence.; Law -- Social aspects -- United States.; Sociologie juridique.; Law -- Social aspects; Sociological jurisprudence; United States